2012
DOI: 10.17221/6349-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the results of hypo-osmotic swelling tests, sperm motility, and fertility in Estonian Holstein dairy bulls

Abstract: ABSTRACT:As an attempt to find an inexpensive and simple laboratory method for artificial insemination (AI) bull semen quality assessment, the osmotic resistance of spermatozoa was measured using the hypoosmotic swelling (HOS) test, developed by Jeyendran et al. (1984) (labelled HOS-1), and its modifications (HOS-2, HOS-3), with decreased osmotic pressure aimed at challenging sperm survival ability. The test results were benchmarked against sperm viability measurements performed using the Computerized Motility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…The Plasma membrane integrity (PM) is essential for survival of sperm in the female reproductive tract and to maintain the fertilizing ability by acting as a selective barrier between components of the intracellular and extracellular environment (Gwathmey et al, 2006). Hypo-osmotic swelling test (HOST) is one of the simplest methods to evaluate the sperm cells plasmalemma stability (Padrik et al, 2012). This method complements with the routine sperm analysis (Nie & Wenzel, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The Plasma membrane integrity (PM) is essential for survival of sperm in the female reproductive tract and to maintain the fertilizing ability by acting as a selective barrier between components of the intracellular and extracellular environment (Gwathmey et al, 2006). Hypo-osmotic swelling test (HOST) is one of the simplest methods to evaluate the sperm cells plasmalemma stability (Padrik et al, 2012). This method complements with the routine sperm analysis (Nie & Wenzel, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Thurston et al (2002) also suggest that the sensitivity of sperm to cryopreservation might be partly related to genetic factors, which could explain variations among species, breeds, and individuals. Padrik et al (2012) reported high correlation between HOS test and sperm motility, and nonreturn rates, which was confirmed by Ramu and Jeyendran (2013). Nevertheless, there was found no effect of MOT in FE on INT after thawing, measured by HOS test, and on dynamics of their changes at both observed volumes.…”
Section: Discussionmentioning
confidence: 59%
“…The fertilization ability is in positive correlation with the percentage of reacted sperm cells. Influx of the fluid due to hypo-osmotic stress causes the sperm tail to coil or swell (Padrik et al 2012). Aliquots of 0.1 ml of fresh semen were mixed with 1.0 ml of Sörensen's buffer (prepared by mixing 2.1492 g Na 2 HPO 4 + 12 H 2 O in 90 ml of distilled water with 0.273 g KH 2 PO 4 in 30 ml distilled water; pre-warmed to 38°C).…”
Section: Methodsmentioning
confidence: 99%
“…O HOST é um dos métodos mais simples e rápidos para avaliar a funcionalidade da membrana plasmática dos espermatozoides. Além disso, o teste é bom preditor de fertilidade, já que a fertilização in vivo do oócito não acontece se a membrana plasmática do espermatozoide estiver bioquimicamente inativa (Perez-Llano et al, 2001;Padrik et al, 2012). Correa et al (1997) descreveram uma alta correlação entre o percentual de espermatozoides funcionalmente íntegros e a fertilidade.…”
Section: Introductionunclassified
“…Correa et al (1997) descreveram uma alta correlação entre o percentual de espermatozoides funcionalmente íntegros e a fertilidade. Por isso, o HOST pode ser utilizado como um método complementar na análise da potentia generandi de um reprodutor (Padrik et al, 2012).…”
Section: Introductionunclassified